Save Your Tears for the Toxicity Assays─Carbon Nanotubes Still Fooling Scientists - Suni, Johanna; Valkama, Salli; Peltola, Emilia (American Chemical Society, 2025)
The extensive study of carbon nanotube (CNT) toxicity stems from their widespread application across various fields. The toxicity of CNTs is commonly assessed using cell viability assays based on tetrazolium salts, such as the MTT assay. ISO 10993–5 outlines the MTT assay and related in vitro cytotoxicity tests as international standards. However, nearly two decades ago, it was observed that MTT interacts with CNTs, potentially yielding inaccurate results. Despite this, the MTT assay remains the most widely used method for studying CNT toxicity in vitro today. Here, we demonstrate that six commonly used tetrazolium salts in cell viability assays─MTT, MTS, INT, XTT, WST-1, and WST-8─ interfere with both single-walled nanotubes (SWCNTs) and multiwalled carbon nanotubes (MWCNTs). According to ISO 10993–5, cell viability percentages below 70% indicate cytotoxicity. At the standard testing duration of 3 h, the absorbance values in the presence of 5 mg/mL of either SWCNT or MWCNT decreased to below 70% relative to the control. At a lower concentration of 0.5 mg/mL, the effect was less pronounced, with the absorbance decreasing to an average of 84% compared to the control. Our results suggest that none of these cell viability assays alone offers a fully reliable method for evaluating CNT toxicity, especially with high CNT concentrations. Therefore, it is essential to carefully assess which in vitro methods are truly suitable for CNT toxicity studies.